ANALISIS PELAKSANAAN AKAD MUDHARABAH PADA USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI BINJAI UTARA KOTA BINJAI (Studi Penelitian Warung Bakso 88 Binjai) - Suwandi Suwandi; Rido Kurniawan, Dhani Rahman Lubis, Marsha Yolanda Chairisqa, Muhammad Nur Iqbal (ADISAM PUBLISHER, 2025)
This research aims to analyze in depth the implementation of mudharabah contracts in the Micro, Small and Medium Enterprises (MSME) sector, with a case study at Warung Bakso 88 Binjai in North Binjai District, Binjai City. The method used is a qualitative approach with a case study design, where data is collected through in-depth interviews, observation and documentation. The focus of the research is directed at understanding how mudharabah contracts are practiced in local social, economic and cultural contexts. The research results show that the implementation of the contract is carried out informally and based on trust, without written documentation, but still upholds sharia principles such as justice, deliberation and moral responsibility (Azmi & Salim, 2021). Even though it does not follow the formal structure as described in the muamalah fiqh literature, the core values of the mudharabah contract are still implemented through strong social relations between capital owners and business managers. This practice shows that sharia economics at the micro level is more flexible and is strongly influenced by local norms that exist in society. This substantive approach to sharia values which is carried out contextually reflects the maqashid of sharia, namely benefit and justice, as the main priority in economic transactions (Yuliani & Fachrurrozi, 2022). This research also found that responsibility in contracts is not only understood in a legal-formal way, but also as a spiritual trust that must be maintained. When the business does not produce a profit, the manager still feels obliged to share the profits, showing that religious ethics is the main driver for the continuity of the contract. This confirms that in microeconomic practice, moral values often have greater power than formal regulations (Rohmah & Prasetyo, 2019). These findings enrich the literature on the implementation of sharia contracts on an MSME scale, and contribute to the importance of a contextual approach in Islamic economics. The implementation of the mudharabah agreement at Warung Bakso 88 is proof that the sharia economic system can run organically in society if it is supported by the values of trust and integrity of business actors. Therefore, adapting Islamic economic theory by considering the local context is very important to answer the challenges and dynamics of the people's economic practices (Sari & Wardani, 2023)